STRATEGI KOMUNIKASI PEMASARAN NESTLE DANCOW CALCIUM PLUS SEBAGAI PRODUK BARU DI PEKANBAR - Sagala, Novita Wardah; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Nestle DCP as a new product has been reached their sales target, but the target to be a market leader has not yet reached. This research aims to determine about the implementation of Nestle DCP marketing communication strategy as a new product research metodh used qualitative with descriptive approach. Located in Jl.Lobak Gg.Kopi No.3 Pekanbaru, from July – November 2014. The subjects were 10 peoples, were taken through purposive technique. While the object is the marketing communication strategy of Nestle DCP as a new product in Pekanbaru. The data collection technique used were observation, interviews and documentation. The data analysis technique researcher used qualitative data analysis according to Huberman and Miles. The data validity examination technique was using participation extention and triangulation. The result of research indicates that marketing communication strategy Nestle DCP as a new product it was by having a sales promotion, establish a commercialise an advertising, doing a personal selling, establish a publicity, contriving a direct marketing, and arranging event/sponsorship. The obstacles is such as the lack of media advertising usage, the lack of budget for promotions, discontinuity of the promotion process, sponsorship activities were performed slightly, competitors activities were more innovative, the Dancow’s brand were too identical with children’s milk product and the publicity effort was not at its best.Key Word: Marketing Communication Startegy, New Product.